A randomised-controlled trial of the effects of very low-carbohydrate and high-carbohydrate diets on cognitive performance in patients with type 2 diabetes. Issue 10 (23rd November 2016) - Tay, Jeannie; Zajac, Ian T.; Thompson, Campbell H.; Luscombe-Marsh, Natalie D.; Danthiir, Vanessa; Noakes, Manny; Buckley, Jonathan D.; Wittert, Gary A.; Brinkworth, Grant D.
Abstract: This study compared the longer-term effects of a very low-carbohydrate, high-fat diet with a high-carbohydrate, low-fat diet on cognitive performance in individuals with type 2 diabetes (T2D). In total, 115 obese adults with T2D (sixty-six males, BMI: 34·6 (sd 4·3) kg/m 2, age: 58 (sd 7) years, HbA1c: 7·3 (sd 1·1) %, diabetes duration: 8 (sd 6) years) were randomised to consume either an energy-restricted, very low-carbohydrate, low-saturated-fat (LC) diet or an energy-matched high unrefined carbohydrate, low-fat (HC) diet with supervised aerobic/resistance exercise (60 min, 3 d/week) for 52 weeks. Body weight, HbA1c and cognitive performance assessing perceptual speed, reasoning speed, reasoning ability, working memory, verbal fluency, processing speed, short-term memory, inhibition and memory scanning speed were assessed before and after intervention. No differences in the changes in cognitive test performance scores between the diet groups were observed for any of the cognitive function outcomes assessed ( P ≥0·24 time×diet). Percentage reduction in body weight correlated with improvements with perceptual speed performance. In obese adults with T2D, both LC and HC weight-loss diets combined with exercise training had similar effects on cognitive performance. This suggests that an LC diet integrated within a lifestyle modification programme can be used as a strategy for weight and diabetes management without the concern of negatively affecting cognitive function.